An objective definition for clinical suspicion of T‐cell‐mediated rejection after liver transplantation. Issue 7 (10th June 2017) - Rodríguez‐Perálvarez, Manuel; De Luca, Laura; Crespo, Gonzalo; Rubin, Ángel; Marín, Sandra; Benlloch, Salvador; Colmenero, Jordi; Berenguer, Marina; Navasa, Miguel; Tsochatzis, Emmanuel; De la Mata, Manuel
Abstract: A uniform definition of clinical suspicion of T‐cell‐mediated rejection (TCMR) in liver transplantation (LT) is needed to homogenize clinical decisions, especially within randomized trials. This multicenter study included a total of 470 primary LT recipients. The derivation cohort consisted of 142 patients who had clinically driven liver biopsies at any time after LT. The external validation cohort included 328 patients who underwent protocol biopsies at day 7‐10 after LT. The rates of moderate‐severe histological TCMR were 33.8% in the derivation cohort and 43.6% in the validation cohort. Independent predictors (ie, risk factors) of moderate‐severe TCMR in the derivation cohort were as follows: serum bilirubin >4 mg/dL (OR=5.83; P <.001), rising bilirubin within the 4 days prior to liver biopsy (OR=4.57; P =.003), and blood eosinophils count >0.1×10 9 /L (OR=3.81; P =.004). In the validation cohort, the number of risk factors was an independent predictor of moderate‐severe TCMR (OR=1.74; P =.001), after controlling for hepatitis C status. The number of risk factors paralleled the rates of moderate‐severe TCMR in the derivation and validation cohorts ( P <.001 in both comparisons). In conclusion, increased serum bilirubin, rising bilirubin and eosinophilia are validated risk factors for moderate‐severe histological TCMR and could be used as objective criteria to select candidates for liver biopsy.